2020
DOI: 10.3390/polym12010209
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Silanization Temperature and Time on the Marching Modulus of Silica-Filled Tire Tread Compounds

Abstract: Marching modulus phenomena are often observed in silica-reinforced solution styrene–butadiene rubber/butadiene rubber (S-SBR/BR) tire tread compounds. When such a situation happens, it is difficult to determine the optimum curing time, and as a consequence the physical properties of the rubber vulcanizates may vary. Previous studies have demonstrated that the curing behavior of silica compounds is related to the degree of silanization. For the present work, the effect of silanization temperature and time on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…The Payne effect can be used to study the filler status, that is, the micro-dispersion of the filler in the rubber. Therefore, a better micro-dispersion of the filler in the matrix would lead to a lower Payne effect [ 7 ]. Observing Figure 10 b, it can be concluded that the dispersion of the silica has an enormous effect on the mechanical properties of the rubber compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Payne effect can be used to study the filler status, that is, the micro-dispersion of the filler in the rubber. Therefore, a better micro-dispersion of the filler in the matrix would lead to a lower Payne effect [ 7 ]. Observing Figure 10 b, it can be concluded that the dispersion of the silica has an enormous effect on the mechanical properties of the rubber compounds.…”
Section: Resultsmentioning
confidence: 99%
“…During this procedure two chemical reactions take place: (i) bonding of the organosilane to the silica surface and (ii) reaction between the silane and the rubber. This mixing method exhibits some disadvantages, such as the need for an additional step to ensure the finalization of the reaction between the silane and the silica and the generation of ethanol as a by-product of the silanization reaction [ 6 , 7 , 8 ]. The first one leads to longer mixing times, the second contains the risk of porosity at the surface of the extrudate.…”
Section: Introductionmentioning
confidence: 99%
“…Many attempts have therefore been made to investigate the parameters influencing the tire performance, especially FSE and WG, for example, rubbers, [2][3][4][5] activators, 6,7 fillers, [8][9][10] silane coupling agents, 11,12 processing oils, [13][14][15] and mixing conditions. 16,17 Focusing on fillers, the balanced tire performance is usually gained in the system containing carbon black/silica (CB/SiO 2 ) hybrid filler. Veiga et al reported that the partial replacement of CB by SiO 2 (15 phr at the replacing ratio of 1:1) with the presence of bis [3-(triethoxysilyl)propyl]tetrasulfide (3 phr) can improve abrasion resistance (~4%), rolling resistance (~10%) and WG (~19%) of the tread vulcanizates.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the silica surface has to be silanized in order to make it hydrophobic [ 5 , 6 ]. The sulfur containing silane coupling agents, such as bis(3-(triethoxysilyl)-propyl) tetrasulfide (TESPT) and bis (3-(triethoxysilyl)-propyl) disulfide (TESPD), are commonly used, which have a potential to create sulfur linkages between silica surface and the unsaturated polymer matrix and greatly improve the polymer–filler interaction [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Compared to the TESPT, TESPD has a higher temperature stability and, therefore, improved scorch during silanization when high mixing temperatures are required.…”
Section: Introductionmentioning
confidence: 99%